Confronting an augmented reality - John Hedberg; Robert Fitzgerald; James Steele; Anna Wilson; Matt Bacon; Danny Munnerley (Association for Learning Technology, 2012)
How can educators make use of augmented reality technologies and practices to enhance learning and why would we want to embrace such technologies anyway? How can an augmented reality help a learner confront, interpret and ultimately comprehend reality itself? In this article, we seek to initiate a discussion that focuses on these questions, and suggest that they be used as drivers for research into effective educational applications of augmented reality. We discuss how multi-modal, sensorial augmentation of reality links to existing theories of education and learning, focusing on ideas of cognitive dissonance and the confrontation of new realities implied by exposure to new and varied perspectives. We also discuss connections with broader debates brought on by the social and cultural changes wrought by the increased digitalisation of our lives, especially the concept of the extended mind. Rather than offer a prescription for augmentation, our intention is to throw open debate and to provoke deep thinking about what interacting with and creating an augmented reality might mean for both teacher and learner.